Application Effect of Four-Subjects and Four-Dimensions Evaluation System in the Classroom Teaching of Geriatric Nursing - Han, Xin; Li, Xiaoling (Pacific International Journal, 2023)
Geriatric nursing is the main course for cultivating elderly nursing talents. The teaching quality of geriatric nursing is the key element of training elderly nursing talents. Therefore, it is of great significance to improve the classroom teaching quality of geriatric nursing. The purpose of this study is to construct a four-subject and four-dimension evaluation system and explore its application effect in geriatric nursing teaching. From February 2022 to July 2022, an experimental study was conducted on 185 sophomore nursing students from Zaozhuang Vocational College. The experimental group adopted the four-subject and four-dimension evaluation system, while the control group adopted the summative evaluation method. The study found that the scores of the experimental group were higher than those of the control group (P<0.05). In addition, the academic evaluation of the experimental group was significantly improved (P<0.05). The results show that the application of four subjects and four dimensions evaluation system in geriatric nursing teaching is conducive to improving students' learning effect and comprehensive ability.